Metformin Improves Autonomic Nervous System Imbalance and Metabolic Dysfunction in Monosodium L-Glutamate-Treated Rats - Franco, Claudinéia Conationi da Silva; Previate, Carina; Trombini, Amanda Bianchi; Miranda, Rosiane Aparecida; Barella, Luiz Felipe; Saavedra, Lucas Paulo Jacinto; de Oliveira, Júlio Cezar; Prates, Kelly Valério; Tófolo, Laize Peron; Ribeiro, Tatiane Aparecida; Pavanello, Audrei; Malta, Ananda; et al. (Frontiers in Endocrinology, 2021)
Metformin is an antidiabetic drug used for the treatment of diabetes and metabolic diseases. Autonomic nervous system (ANS) imbalance is associated with metabolic diseases. The aim this study was to test whether metformin could improve ANS activity in obese rats. Obesity was induced by neonatal treatment with monosodium L-glutamate (MSG). From twenty-one-day-old to 100-day-old, MSG-rats were treated with metformin 250 mg/kg body weight/day, or saline. Rats were euthanized to biometric and biochemical parameters evaluation. ANS electrical activity was recorded. Metformin normalized the hyper vagal response in MSG-rats. Insulin secretion stimulated by glucose in isolated islets was increased in MSG rats, while, cholinergic response was reduced. Metformin treatment normalized the cholinergic response, which involved mostly the pancreatic beta cell muscarinic receptor type M3mAChR. Protein expression of muscarinic receptors M3mAChR was increased in MSG-obesity rats; while metformin treatment decreased the expression by 25%. In conclusion chronic metformin treatment was effective to normalized ANS activity and alleviating obesity in MSG-rats.